1997
DOI: 10.1093/cercor/7.7.635
|View full text |Cite
|
Sign up to set email alerts
|

Cortical structure predicts the pattern of corticocortical connections

Abstract: Cortical areas are linked through pathways which originate and terminate in specific layers. The factors underlying which layers are involved in specific connections are not well understood. Here we tested whether cortical structure can predict the pattern as well as the relative distribution of projection neurons and axonal terminals in cortical layers, studied with retrograde and anterograde tracers. We used the prefrontal cortices in the rhesus monkey as a model system because their laminar organization var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
473
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(505 citation statements)
references
References 50 publications
31
473
0
1
Order By: Relevance
“…It is also possible that the classical anatomical classification of FF and FB projections does not apply to heteromodal projections when it comes to interactions between sensory modalities. This would support the hypothesis according to which the anatomical pattern of the cortico-cortical connections that involve the polysensory areas of the frontal lobe depend on the intrinsic architecture of areas linked together in terms of laminar differentiation (Barbas and Rempel-Clower, 1997;Rempel-Clower and Barbas, 2000). How this rule of a structural dependence about the laminar organization of projections affects heteromodal connections remains to be determined.…”
Section: Primary Sensory Areas Receive Non-specific Inputssupporting
confidence: 69%
“…It is also possible that the classical anatomical classification of FF and FB projections does not apply to heteromodal projections when it comes to interactions between sensory modalities. This would support the hypothesis according to which the anatomical pattern of the cortico-cortical connections that involve the polysensory areas of the frontal lobe depend on the intrinsic architecture of areas linked together in terms of laminar differentiation (Barbas and Rempel-Clower, 1997;Rempel-Clower and Barbas, 2000). How this rule of a structural dependence about the laminar organization of projections affects heteromodal connections remains to be determined.…”
Section: Primary Sensory Areas Receive Non-specific Inputssupporting
confidence: 69%
“…The findings in this group, nevertheless, also agree with our hypothesis of anterior-increase and posterior-decrease in rCBF. Our subjects with temporal lobe epilepsy show frontal-parietal increases as well, although these increases are shifted to the side contralateral to the seizure focus, which may reflect an interaction of the temporal epileptogenic focus with the temporal-frontal connections that go from the middle temporal gyrus to the middle frontal gyrus (Barbas and Rempel-Clower 1997). These results agree with those produced by clonidine as reported by Moffoot et al (1994) in Korsakoff's subjects, but differ from those reported by Coull and colleagues (1997) in controls treated with clonidine.…”
Section: Discussionmentioning
confidence: 63%
“…In contrast to layer II/ III neurons, none of the electrophysiological signatures of aging among layer V neurons correlate with cognitive performance (Luebke and Chang 2007;Luebke and Amatrudo 2010). Thus, within PFC area 46, it is the layer II/III corticocortical pyramidal neurons, and not the layer V neurons that contribute to the corticostriatal-thalamic-cortical circuitry, that are thought to be crucial for cognitive capacities vulnerable to the effects of aging (Barbas and Rempel-Clower 1997;Luebke and Chang 2007;Luebke and Amatrudo 2010).…”
Section: Pfc Neuronsmentioning
confidence: 99%